Käte Hamburger og »digtningens logik« - Hansen, Nils Gunder (K&K - Kultur og Klasse, 2006)
Käte Hamburger, and »the logic of literature« This paper examines the principal content and line of thought in Käte Hamburger’s classic study on the character of fiction, Die Logik der Dichtung, from 1957. Hamburger’s book is an ambitious and original attempt to relate the differences of literary genres and the reader’s phenomenological experience of these differences to linguistic circumstances and a theory of enunciation. The paper first develops the theory of enunciation that marks Hamburger’s linguistic point of departure and thereafter carefully examines her points on epic fiction (third-person narration), which stands as the cornerstone of her theory of fiction. Subsequently her »logical« definitions of lyric poetry, first-person narration, drama and film are summarized. The paper concludes that the work of Hamburger contains extremely valuable contributions to a theory of fiction, but several arguments of both a theoretical and a more pragmatic nature can be raised against it. Furthermore her theory of fiction seems to rest on premises inspired by existential ontology, and these premises remain somewhat blurred.